Ответ:
1)(x+4)²=5x+40
x²+8x+16=5x+40
x²+8+16-5x-40=0
x²+5x-24=0
D=5²-4•1•(-24)=25+96=121
x½=-5±√121=5±√11
2•1 2
x¹=3
x²=8
2)3(x²+x)=2(8x-7)
3x²+3x= 16x-14
3x²-3x+16x+14=0
3x²-13x+14=0
D=169-4•3•14=169-168=1
x½=13±√1=13±1
2•3 6
x¹=2⅓
x²=2
3)5x²-11x+2=0
D=(-121)-4•5•2=121-40=81
x½=11±√81=11±√9
2•5 10
x¹=2
x²=⅕
4)2x²-5x-3=0
D=5²-4•2•(-3)=25+24=49
x½=-5±√49=5±√7
2•2 4
x¹=-0,5
x²=3
5) x(x+5)=104
x²+5x=104
x²+5x-104=0
D=25-4•1•(-104)=25+416=441
x½=5±√441=5±21
x¹=8
x²=-13
6) x²=(x-3)²+(x-6)²
x²=x²-6x+9+x-12+36
x²-18x+45=0
D=324-4•1•45=324-180=144
x½=18±√144=18±12
x²=15
7)5x²-8x+3=0
D=64-4•5•3=64-60=4
x½=8±√4=8±2
x¹=1
x²=⅗
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1)(x+4)²=5x+40
x²+8x+16=5x+40
x²+8+16-5x-40=0
x²+5x-24=0
D=5²-4•1•(-24)=25+96=121
x½=-5±√121=5±√11
2•1 2
x¹=3
x²=8
2)3(x²+x)=2(8x-7)
3x²+3x= 16x-14
3x²-3x+16x+14=0
3x²-13x+14=0
D=169-4•3•14=169-168=1
x½=13±√1=13±1
2•3 6
x¹=2⅓
x²=2
3)5x²-11x+2=0
D=(-121)-4•5•2=121-40=81
x½=11±√81=11±√9
2•5 10
x¹=2
x²=⅕
4)2x²-5x-3=0
D=5²-4•2•(-3)=25+24=49
x½=-5±√49=5±√7
2•2 4
x¹=-0,5
x²=3
5) x(x+5)=104
x²+5x=104
x²+5x-104=0
D=25-4•1•(-104)=25+416=441
x½=5±√441=5±21
2•1 2
x¹=8
x²=-13
6) x²=(x-3)²+(x-6)²
x²=x²-6x+9+x-12+36
x²-18x+45=0
D=324-4•1•45=324-180=144
x½=18±√144=18±12
2•1 2
x¹=3
x²=15
7)5x²-8x+3=0
D=64-4•5•3=64-60=4
x½=8±√4=8±2
2•5 10
x¹=1
x²=⅗